(untitled) (Journal of the College of Basic Education, 2022)
Our topic is important because of the necessity of folding the artificial borders between reason and imagination, philosophy and literature, content and form, meaning and articulation, material and image, thought and language, morals and beauty, religion and art, so why do we need a harmonious and integrated cultural discourse that embodies the integration of the faculties and powers of the human soul, a discourse that rejects The monolithic view of things, and fanaticism for a party at the expense of one party, and our philosophers embodied in their critical propositions something of this desired integration and equalization, which took criticism in some aspects from the naive proposition, as is the case in the question of word and meaning, for example . Perhaps our Aristotelian philosophers, in particular, have fallen into some confusion and confusion, as they reconcile Aristotle’s artistic philosophy and Arabic literature, never denying that what they have taken is a systematic step at the core, provided that we consider the reckoning of the beginnings that are often not without some pitfalls, a literature of etiquette, However, cross-fertilization between morals and cultures remains at all levels a matter entrusted to the law of evolution, and when its hour comes, it will occur despite the nose of every opponent, and this is one of the bright signs of God in his creation